2017
DOI: 10.1007/s10068-017-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l-lysine on thermal gelation properties of chicken breast actomyosin

Abstract: The effects of l-lysine (l-Lys) on the water holding capacity (WHC) and texture of actomyosin (AM) gel and the possible mechanisms were investigated. l-Lys increased the WHC and hardness of the AM gel. These effects may be related to the even and continuous microstructure of the gel according to the scanning electron microscopy analysis. Furthermore, l-Lys increased the surface hydrophobic residues and the reactive sulfhydryl groups. l-Lys decreased the storage modulus at the first transition temperature but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…reported that the addition of basic amino acids can expose buried hydrophobic groups and reactive sulfhydryl groups and contribute to an enhanced protein gelation (Guo et al, 2015;Lei et al, 2016;Lei et al, 2017).…”
Section: Appearance and Color Of Wpi Gelsmentioning
confidence: 99%
See 4 more Smart Citations
“…reported that the addition of basic amino acids can expose buried hydrophobic groups and reactive sulfhydryl groups and contribute to an enhanced protein gelation (Guo et al, 2015;Lei et al, 2016;Lei et al, 2017).…”
Section: Appearance and Color Of Wpi Gelsmentioning
confidence: 99%
“…The addition of basic amino acids modified the texture of the WPI gels. Several studies have demonstrated that basic amino acids strongly bind to the charged residues of proteins through electrostatic interactions, which alters the structure and thermal properties of the proteins and in turn affect their gelling properties (Guo et al, 2015;Lei et al, 2016;Lei et al, 2017;. Gel hardness and gumminess increased significantly (P < 0.05) at pH 7.59 when 0.5% arginine was added.…”
Section: Texture Profile Analysismentioning
confidence: 99%
See 3 more Smart Citations